DETERMINANTS OF FIXED ASSET REVALUATION DECISIONS WITH FIRM SIZE AS A MODERATING VARIABLE - Safitri, Nur Havifa; Kholilah, Kholilah (Jurnal Aplikasi Akuntansi, 2025)
This study uses firm size as a moderating variable to investigate how fixed asset revaluation decisions are impacted by fixed asset intensity, debt, liquidity, operating cash flow, and company growth. All of the study's objects are businesses in the financial industry that are listed on the IDX. Purposive sampling yielded 90 organizations with a total observation data of 450 based on the following criteria: companies listed on the IDX in 2019-2023, publishing complete annual reports in 2019-2023, having fixed assets consecutively during 2019-2023, and companies that use rupiah currency are 90 companies with a total observation data of 450. The collected data were analyzed using logistic regression and moderation regression analysis for hypothesis testing. The results showed that the decision to revalue fixed assets is influenced by both fixed asset intensity and liquidity, indicating that businesses with high fixed asset intensity and low liquidity are more likely to decide to revalue. Leverage, operating cash flow, or company development have no impact. This result suggests that elements influencing a firm's decision to revalue its fixed assets are not leverage, operating cash flow, or company growth. The impact of debt and liquidity on fixed asset revaluation choices is then reinforced by business size as a moderating element. The implications of this research indicate that the revaluation method can enhance the relevance and quality of the information presented in financial statements because the motivation for revaluing fixed assets is to obtain information related to the fair value of fixed assets. Management policies for evaluating fixed assets are one way to improve the company's performance.